Bone Health Index (BoneXpert) and parameters of peripheral quantitative computed tomography indicate overall adequate bone health in adolescents with chronic endocrine diseases at time of transition - Sebastian Gippert; Markus Bettendorf; Johannes Hoos; Daniela Choukair (PLoS ONE, 2025)
Background/Aim Low bone mass is common in children and adolescents with chronic endocrine disorders. Peripheral quantitative computed tomography (pQCT) is used to quantify bone health. A new automated Bone Health Index (BHI) determination (BoneXpert TM ) is available using digitized X-rays of the left hand taken for bone age (Greulich&Pyle, BA) determination. In this study, we determine the BHI in adolescents with various endocrine disorders and compare it to conventional pQCT indices to evaluate the BHI as a potential surrogate parameter for bone health and muscle strength in adolescents. Methods 134 adolescents (70 females) with chronic endocrine diseases and a median age of 17.6 years (IQR: 16.4,19.4) were included at the time of transition. Diagnoses were growth hormone deficiencies (GHD, n = 37), Turner syndrome (TS, n = 27), congenital adrenal hyperplasia (CAH, n = 22), small for gestational age (SGA, n = 20), multiple pituitary hormone deficiency (MPHD, n = 17) and Klinefelter syndrome (KS, n = 11). BA and BHI were assessed by BoneXpert™ (available for 104 patients) and were compared to a random subgroup with available pQCT parameters (n = 38: 13 CAH, 12 GHD, 7 TS and 6 SGA) assessed by XCT-2000 scanner. Further, grip strength was assessed by hand dynamometer (n = 134). Results Median BHI-SDS for all patients available was −0.66 (IQR: −1.50,0.18, n = 104), lowest in patients with CAH (−1.04, IQR: −2.34,0.22, n = 22). The majority of patients (58.6%) had a BHI-SDS greater than −1, indicating adequate bone health. Median pQCT parameters and median grip strength showed a z-score greater than −1, suggesting an appropriate muscle strength for most patients. Patients with both available BHI-SDS and pQCT parameters (n = 32) showed significant positive correlations with several measurements: bone mineral content (65%) SDS (ρ = 0.576, p < 0.001); metaphyseal (4%) site total BMD SDS (ρ = 0.492, p = 0.005); total cross-sectional area SDS (ρ = 0.379, p < 0.032) and SSI SDS (ρ = 0.417, p = 0.018). In addition, BHI-SDS correlated positively with muscle cross-sectional area SDS (ρ = 0.352, p = 0.066, n = 32) and grip strength SDS (ρ = 0.205, p = 0.050, n = 104). Conclusions At the time of transition, the bone health of adolescents with chronic endocrine diseases is mostly appropriate, as estimated by BoneXpert TM and pQCT. Grip strength was also adequate in the majority of patients. In addition, this study is the first to demonstrate a significant correlation between these methods in adolescents. Consequently, the BHI has the potential to be an effective screening tool for assessing bone health, characterized by wide availability and low radiation exposure, though additional analyses are needed.